USING THE” OPPOSITE ATTITUDE " STRATEGY ON THE TOPIC OF WORLD ECONOMY AND INTERNATIONAL DIVISION OF LABOR OF THE COURSE “SOCIO-ECONOMIC GEOGRAPHY OF THE WORLD” GRADE 10 (World Bulletin of Management and Law, 2023)
This article describes the use of the “confrontation attitude” strategy on the topic of world economy and international division of labor of the 10th grade course “socio-economic geography of the world”.